Terapi Bermain Meniup Baling-Baling Menurunkan Intensitas Nyeri Pada Pemasangan Infus Anak Prasekolah - Meily Nirnasari; Liza Wati (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
Infusionis an invasive procedure that causes pain in children. Wich one strategy that can help reduce the pain is non-pharmacological measures that easy, can be done by nurses to reduce the pain during invasive procedure in children is a deep breathing relaxation techniques using play therapy blow propeller. The purpose ofstudythis was to know the effect of play therapy blowing propeller to decrease of pain infusion. Data collection was conducted from March-April 2018 at Raja Ahmad Thabib Hospital Tanjungpinang. using design quasyexperimental approach only with posttest control group design. The sampling technique is consecutive sampling with the number 20 preschool children (2-6 years), 10 in the experimental group and 10 control group. Pain during infusion in children measured directly with a scale FLACC (Face,Legs, Activity, Cry,Consolability). The data analysis was performed with thetest Mann-Whitney to assess pain intensity difference between the intervention and control groups. These results indicate the existence of significant differences in pain scores p-value= 0.01(pv <0.05) between the intervention and control group at the time of infusion. This research may help to nurses and other health workers as non-pharmacological techniques when IVs that child pain intensity lighter.Keywords: Installation Infusion, Pain, Relaxation Breath deeply